Konsep Legalisasi dalam Politik Kerjasama Internasional - Nanang Pamuji Mugasejati (Jurnal Ilmu Sosial dan Ilmu Politik, 2006)
The institutionalization of various international co-operations has lead to the creation of legalization as a new concept for understanding international politics. Some view that the emergence of legalization brings to the questions of academic inquiries in the study of international relations, worrying that this will substantially deal with legal aspects. This article observes the position of legislation as a product of political process.